Digital Innovation and Curriculum Reform in Islamic Boarding Schools of Serambi Mekah: Balancing Tradition and Modernity - Novebri, Novebri; Kurniady, Dedy Achmad; Komariah, Aan; Suryana, Asep (Tadbir : Jurnal Studi Manajemen Pendidikan, 2025)
Pesantren as traditional Islamic educational institutions, are increasingly challenged to balance the preservation of religious values with technological adaptation in the era of Society 5.0. This study investigates how pesantren in Padang Panjang City, West Sumatra, implement digital educational innovations while maintaining their core identity. Guided by the central question—how do pesantren integrate technological advancements into their educational practices without compromising their traditional foundations? this research adopts a narrative-based grounded theory approach. Data were obtained through observation, interviews, and document analysis in six selected pesantren. Findings reveal three key areas of innovation: integration of the national and pesantren curricula, incorporation of digital technologies into the learning process, and the development of extracurricular programs tailored to students’ talents and interests. Some pesantren have established specialized units such as the Diniyyah Research Center and Diniyyah Robotic, introduced native speakers in language programs, and facilitated research, literacy, and tech-based learning activities. These developments reflect not only adaptive capacity but also the emergence of a contextual and forward-looking Islamic education model. The study contributes to a nuanced understanding of how pesantren navigate transformation while upholding their educational and spiritual heritage in response to 21st-century demands.